THE GEOPOLITICS OF CRITICAL MINERALS: AN INTERNATIONAL RELATIONS PERSPECTIVE ON INDONESIA’S NICKEL DOWNSTREAM POLICY - Nofirman, Nofirman; Anwar, Shamsul; Haji Ali, Azimah; Magar, Bina (Cognitionis Civitatis et Politicae, 2026)
The global race for critical minerals has transformed nickel into a strategic asset in contemporary geopolitics. Indonesia, possessing one of the world’s largest nickel reserves, has adopted a downstream policy to assert greater control over its mineral resources and strengthen national economic sovereignty. This study aims to analyze Indonesia’s nickel downstream policy from an international relations perspective, emphasizing its geopolitical, economic, and strategic implications. Using a qualitative method with a descriptive-analytical approach, the research draws on policy documents, trade data, and scholarly discourse to interpret Indonesia’s positioning within global power dynamics. The findings reveal that the policy reflects Indonesia’s attempt to transition from a resource supplier to a value-added industrial hub, balancing between China’s technological dominance and Western market access. Moreover, the policy redefines Indonesia’s bargaining power in international trade and its alignment in global supply chains for electric vehicles and renewable energy. The study concludes that Indonesia’s nickel strategy represents a form of resource nationalism adapted to 21st-century multipolar competition, offering insights into how developing nations can leverage critical minerals for geopolitical advantage.